The role of de novo mutations in the development of amyotrophic lateral sclerosis - Doormaal, Perry T.C.; Ticozzi, Nicola; Weishaupt, Jochen H.; Kenna, Kevin; Diekstra, Frank P.; Verde, Federico; Andersen, Peter M.; Dekker, Annelot M.; Tiloca, Cinzia; Marroquin, Nicolai; Overste, Daniel J.; Pensato, Viviana; et al. (Human mutation, 2017)
The genetic basis combined with the sporadic occurrence of amyotrophic lateral sclerosis (ALS) suggests a role of de novo mutations in disease pathogenesis. Previous studies provided some evidence for this hypothesis; however, results were conflicting: no genes with recurrent occurring de novo mutations were identified and different pathways were postulated. In this study, we analyzed whole‐exome data from 82 new patient‐parents trios and combined it with the datasets of all previously published ALS trios (173 trios in total). The per patient de novo rate was not higher than expected based on the general population (P = 0.40). We showed that these mutations are not part of the previously postulated pathways, and gene–gene interaction analysis found no enrichment of interacting genes in this group (P = 0.57). Also, we were able to show that the de novo mutations in ALS patients are located in genes already prone for de novo mutations (P < 1 × 10‐15). Although the individual effect of rare de novo mutations in specific genes could not be assessed, our results indicate that, in contrast to previous hypothesis, de novo mutations in general do not impose a major burden on ALS risk. In this study we analyzed whole‐exome data from 82 new patient‐parents trios and combined it with the datasets of all previously published amyotrophic lateral sclerosis trios (173 trios in total). Using multiple analysis methods, we show that de novo mutations do not impose a major burden on amyotrophic lateral sclerosis risk.